Search for genetic variants of the SYNTAXIN 1A (STX1A) gene: the -352 A>T variant in the STX1A promoter associates with impaired glucose metabolism in an Italian obese population - Romeo, S; Sentinelli, F; Cavallo, M.G; Leonetti, F; Fallarino, M; Mariotti, S; Baroni, M (International Journal of Obesity, 2008)
Objective: To test if sequence variations of the SYNTAXIN 1A ( STX1A ) gene contribute to the susceptibility to type 2 diabetes in a cohort of overweight/obese subjects. Methods: A total of 717 overweight/obese individuals underwent oral glucose tolerance test and were stratified in four groups according to fasting and 2 h glucose levels (NGT, IGT, CGI, T2DM), representing the natural history of diabetes from normal glucose tolerance to overt disease. These subjects were analysed by a two-step genetic study. Functional analysis was performed by electrophoretic mobility shift assay (EMSA) and by supershift with CCAAT/enhancer-binding protein (C/EBP)β antibody. Results: Among the several sequence variations detected in the STX1A gene, the T allele of the −352 A>T single nucleotide polymorphism in the promoter was found in a lower frequency in the subset of individuals with greater impairment of insulin secretion (CGI). To confirm that a lower frequency of the T allele was associated with this condition, we genotyped a second group of 202 overweight/obese individuals with type 2 diabetes, and the frequency of the T allele was reduced in this group also ( P <0.01). Logistic regression confirmed a protective odds ratio (0.49, P <0.01) for the T allele. The EMSA showed that the PRM −352 A allele binds transcription factors with lower affinity compared to the T allele, and incubation with C/EBPβ antibody ‘supershifted’ the complex, indicating that C/EBPβ had a different binding with the PRM −352T allele. Conclusion: A lower frequency of the PRM −352T allele of the STX1A gene was observed in overweight/obese subjects with impaired glucose regulation, particularly among individuals with combined glucose intolerance and overt diabetes. Both these groups have a greater defect in β-cell function compared to normal and glucose intolerant subjects, and this association together with the functional study suggests a possible role of the PRM −352 A>T variant in insulin secretion.